Enhancement of bacteriocin production and antimicrobial activity of pediococcus acidilactici HA-6111-2 - Garcia, J. M. (2017)
The effect of sequential treatments of pressure (50-150 MPa, 10 degrees C, 5 min) and temperature (57 degrees C, 15 min) on the survival and bacteriocin production of Pediococcus acidilactici HA-6111-2 cells in the exponential growth phase was assessed. The growth curves were fi tted with the modifi ed Gompertz model, and the estimated maximum specifi c growth rate was considered to be pressure dependent. A delay in the maximum value of bacteriocin production was registered for more severe pressure conditions, but it was found more notorious for pressure followed by temperature treatments. At lower pressure intensity treatment, regardless of the application order, there was an enhancement of bacteriocin production per cell when compared to the control while maintaining the maximum production value. Bacteriocin production after the treatments can be described by an exponential model.